Complex clinical manifestations and new insights in RNA sequencing of children with diabetes and WFS1 variants - Ding, Yu; Li, Zhe; Zhang, Qianwen; Li, Niu; Chang, Guoying; Wang, Yirou; Li, Xin; Li, Juan; Li, Qun; Yao, Ru-en; Li, Xin; Wang, Xiumin (Frontiers in Endocrinology, 2023)
Background: WFS1-related disorders involve a wide range of clinical phenotypes, including diabetes mellitus and neurodegeneration. Inheritance patterns of pathogenic variants of this gene can be autosomal recessive or dominant, and differences in penetrance present challenges for accurate diagnosis and genetic counselling. Methods: Three probands and one elder brother from three families were systematically evaluated and the clinical data of other family members were collected from the medical history. Whole-exome sequencing was performed on the probands, and RNA sequencing was performed on four patients, their parents with WFS1 variants, and four gender- and age-matched children with type 1 diabetes mellitus. Results: There were six patients with diabetes. Dilated cardiomyopathy, a rare manifestation of WFS1-related disease, was identified in one patient, along with MRI findings of brain atrophy at age 7 years and 3 months, the earliest age of discovery we know of. Whole-exome sequencing revealed five pathogenic or likely pathogenic variants in the WFS1 gene, including c.1348dupC (p.His450Profs*93), c.1381A>C (p.Thr461pro), c.1329C>G (p.Ser443Arg), c.2081delA (p.Glu694Glyfs*16), c.1350-1356delinsGCA (p.His450Glnfs*26), of which 3 variants (c.1348dupC, c.2081delA, c.1350-1356delinsGCA) were novel that have not been previously reported. The differentially expressed genes were mainly associated with immune-related pathways according to the Gene Ontology enrichment analysis of the RNA sequencing data. The exon 1 region of HLA-DRB1 in two patients was not transcribed, while the transcription of the region in their parents was normal. Conclusion: This study emphasizes the clinical and genetic heterogeneity in patients, even in the same family with WFS1 variants. MRI evaluation of the brain should be considered when WFS1-related disorder is first diagnosed.